Design and Development an Ergonomic Transfer Lifter Assistor From Wheelchair To Bed Transfer For Patients Under 50kg - Chicha Bagu; Hatimi Mudi; Fethma M Nor (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2021)
Moving a patient from their bed to some other places for daily routine is such hard work. Caregiver usually using a wheelchair to move a patient from place to place. Nevertheless, they are facing a problem in lifting the patient from bed to wheelchair. The caregiver needs to use lots of energy to lift the patient into a wheelchair, and it may take a long time. This study focuses on design and develop a transfer lifter assistor to assist the caregiver move the patient from bed to another place. It was flexible and easy to conduct. This innovation's advantages are that the height could be adjusted, making the patient more comfortable to sit on from a bed. The size could be adjusted up to 3 and a half feet. The structure mostly from steel and can be disassembled for storage purposes. The result shows that Transfer Lifter Assistor can perform effectively to lift patients with a maximum weight of 50 kilograms. It can support one patient at a time. This innovation has been successfully produced with cost-effective and can be owned by everyone.